ROAD PERFORMANCE ANALYSIS TRACK OF TOURISM OBJECT AIR BATU OF GEOPARK MERANGIN - Radinal Radinal; Bayu Eka Perdana; Sucitra Wijaya (Jurnal Cakrawala Ilmiah, 2022)
Merangin is one of the districts in Jambi Province, Indonesia. Its area is 7,668.61 kmÂ² with a population of 335,000 people. This district is a division of the Sarolangun-Bangko district and is divided into 24 sub-districts which are further divided into 10 sub-districts and 205 villages. Merangin Geopark is located in Air Batu Village, Renah Pembarap District, Merangin Regency and is one of the tourist destinations in Merangin Regency. The Merangin Geopark is a connecting road between villages, thus this road plays an important role in serving a fairly large traffic flow at certain times. A tourist attraction is a place or natural state that has natural resources that are built and developed so that it has an attraction that is cultivated as a place visited by tourists. One of the attractions in Merangin Regency is Air Batu Tourism Object which is located in Air Batu village and Baru village, Renah Pembarap District with a population of 12,987 people and is part of the Merangin Geopark. In this final project the research method used is a quantitative research method. Quantitative research method is a systematic scientific research on the parts and phenomena and the causality of their relationships. The purpose of quantitative research is to develop and use mathematical models, theories and hypotheses related to natural phenomena. The data needed include primary data (road geometric data, traffic volume data, vehicle speed data, side barriers data) and secondary data (map of research location, population data). From the results of the calculation and analysis of the road segment in December 2021, the traffic flow value (Q) = 875 pcu/hour, capacity value (C) = 1617.61 pcu/hour, degree of saturation (DS) = 0,54, free flow speed (FV) = 43,69 km/hour, and the level of service (Level Of Service/LOS) is categorized as level B. Based on the results of calculations carried out in 2022, the Air Batu Geopark Merangin Tourism Object Road section does not require immediate action